2003
DOI: 10.1099/vir.0.18989-0
|View full text |Cite
|
Sign up to set email alerts
|

Infection of macaques with simian immunodeficiency virus induces a species-specific antibody response to major histocompatibility complex class I and class II molecules

Abstract: Envelopes of retroviruses, including human immunodeficiency virus and simian immunodeficiency virus (SIV), contain host cell proteins that potentially represent novel targets for vaccine development. We show here that sera from rhesus macaques recognized simian major histocompatibility complex (MHC) molecules in response to infection with SIV. Antibodies from these animals did not cross-react with human MHC antigens on mitogen-activated peripheral blood mononuclear cells. The development of antibodies to MHC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This may explain the induction of natural antibodies in cardiac transplant candidates with or without VAD, infection, or leukocyte-depleted blood transfusion. 15,16 Therefore, the assignment of antibodies must be carefully analyzed to reduce the rate of unnecessary exclusion of patients who would otherwise receive a transplant.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the induction of natural antibodies in cardiac transplant candidates with or without VAD, infection, or leukocyte-depleted blood transfusion. 15,16 Therefore, the assignment of antibodies must be carefully analyzed to reduce the rate of unnecessary exclusion of patients who would otherwise receive a transplant.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that alloimmunization in macaques may protect them against SIV infection (Stott, 1994). Antibodies to class I and class II molecules have been found in macaques immunized (Bergmeier et al, 1994) or infected (Polyanskaya et al, 2003) with SIV. Xenoimmunization of macaques significantly increased the concentration of CD8-derived suppressor factor (CD8-SF), CCL5, CCL3 and CCL4 (RANTES, MIP-1a and MIP-1b, respectively), which are associated with protection against SIV infection (Wang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…[4] Their results demonstrated that a whole virus vaccine is highly effective in inducing immune responses that can protect against lentivirus infection and AIDS-like disease. However, 3 years later by Arthur et al .,[5] and simultaneously in 2003 by Natasha et al .,[6] it was found that the protective effect was mediated by antigens (such as human leucocytes antigen HLA and β2 microglobulin from the human cells which were used to grow the viral strain.…”
Section: Reviewmentioning
confidence: 99%